Level Of Satisfaction Red Rice Farmers Partnering With PT. Sirtanio Organik Indonesia In Banyuwangi - Fariz Irzat Arifin; Triana Dewi Hapsari (Universitas Muhammadiyah Jember, 2020)
Organic farming systems are developed to produce healthy food and free from chemicals. PT. Sirtanio Organic Indonesia (PT. SOI) is a company producing organic red rice in Banyuwangi. PT. SOI was partnering with red rice farmers as a provider of raw materials needed. Partnerships with farmers are carried out with a contract system that applies to only one planting season. The employment contract makes the number of farmers who partnered every planting season to be different. The research purpose was to identify the level of satisfaction of organic red rice farmers who partnered with PT. SOI. The research area was determined purposively, and analysis methods using descriptive, analytical methods using CSI and IPA. The results of the study showed that the satisfaction level of the organic red rice farmers who made a partnership with PT. SOI is very satisfying, with a CSI value of 85.31%. Two attributes cause farmers to feel very satisfied with the services provided, namely the price of grain offered and the time of payment of agro-input loans.